'Carcinoma en cuirasse' in the neck: extremely unusual initial presentation of gastric cancer. Issue 4 (30th April 2019) - Rajeshwari, Madhu; Sakthivel, Pirabu; Sikka, Kapil; Jain, Deepali
Abstract : Cutaneous metastasis from visceral malignancy is a relatively rare phenomenon. It is even rarer to have cutaneous lesions as the first mode of clinical presentation in such malignancies. The lesions are usually nodular, although they can have varied appearances. Common sites of primaries include breast, lung, colorectum, kidney, ovary, and headandneck. We report an unusual form of cutaneous metastasis in the neck, known as 'carcinoma en cuirasse', in an elderly man that subsequently led to the diagnosis of an occult gastric cancer. Our case highlights the importance of recognising cutaneous metastatic lesions early, as they may herald the diagnosis of an occult internal malignancy.